Development of a Simple Carrying Frame-Type Back Muscle Supporter - OHNISHI, Kengo; SHIMIZU, Seiji; MIURA, Atsuyoshi; KOBAYASHI, Mitsuko; IMADO, Keiji; HIMENO, Toshiko; ITO, Tomoko (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
A simple structured back muscle supporter was developed and evaluated in this study. Many caregivers suffer from pain in the lower back due to severe working conditions. Though hoists and lifts are available, they are rarely used because of drawbacks related to usability. We have developed a carrying frame shape prototype that remarkably reduces lower back burden on caregivers without restricting natural movement of the body. According to the analysis carried out on a mechanical model of a person wearing the supporter, the device generates support moment of 30Nm at the torso flexion angle of 60 degrees. Experimental results show that the EMG amplitude of the erector spinae muscle decreases significantly by wearing this supporter.